2010
DOI: 10.1097/ta.0b013e3181ce1eed
|View full text |Cite
|
Sign up to set email alerts
|

Early Prognosis of Severe Traumatic Brain Injury in an Urban Argentinian Trauma Center

Abstract: : This study provides rigorous, prospective data that (1) validates the generalizability of the five World Health Organization/Organization Mondiale de la Santé TBI prognostic predictors outside of the developed world, and (2) provides outcome benchmarks for mortality and morbidity from severe TBI in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
0
27
0
2
Order By: Relevance
“…Thus, for LMICs, the study provided concrete information on which to base resource-allocation decisions, and documented the clinical success of a treatment approach that is sustainable in low-resource environments. Sufficiently skilled clinical staff with a better organized protocol of care could produce good recovery results in the intensive care unit (ICU) without data from an ICP monitor by using clinical assessment to manage intracranial hypertension [53][54][55][56] .…”
Section: Lessons Learned From Clinical Neurotrauma Researchmentioning
confidence: 99%
“…Thus, for LMICs, the study provided concrete information on which to base resource-allocation decisions, and documented the clinical success of a treatment approach that is sustainable in low-resource environments. Sufficiently skilled clinical staff with a better organized protocol of care could produce good recovery results in the intensive care unit (ICU) without data from an ICP monitor by using clinical assessment to manage intracranial hypertension [53][54][55][56] .…”
Section: Lessons Learned From Clinical Neurotrauma Researchmentioning
confidence: 99%
“…Severe TBI is defined as TBI with initial Glasgow coma scale ≤ 8 after resuscitation. It threatens life on short term and can lead to persisting neurologic disability which puts a heavy socio-economic burden on the entire society, families and individuals [1]- [11]. Severe TBI is the 3 rd leading cause of death in industrialized countries and according to the WHO it might become the leading cause of death and disability worldwide by the year 2020 [1] [8].…”
Section: Introductionmentioning
confidence: 99%
“…No study has reported the prevalence in Africa. Only 2 of the 21 studies were from developing countries (7.33% from Kelantan, Malaysia and 0.68% from Rosario, Argentina) (Petroni et al, 2010;Selladurai et al, 1992) The overall prevalence in developing countries is 6.3%, which is higher than the overall prevalence of 2.8% in developed countries. The quality and availability of emergency and intensive care services differs among different regions.…”
Section: Locationmentioning
confidence: 77%
“…After 2324 duplications removed, 1930 additional articles were excluded on the basis of their titles or abstracts, resulting in the full text of 341 articles being examined. Finally, 20 articles reporting 21 cohort studies were included in the present analysis (Andriessen et al, 2011;Fearnside, Cook, McDougall, & McNeil, 1993;Foulkes, Eisenberg, Jane, Marmarou, & Marshall, 1991;Gomez et al, 2000;Heiden, Small, Caton, Weiss, & Kurze, 1983;Jourdan et al, 2013;Judson, Cant, & Shaw, 1990;Lannoo et al, 2000;Mamelak, Pitts, & Damron, 1996;; L. S. Myburgh et al, 2008;Nordstrom, Messeter, Sundbarg, & Wahlander, 1989;Pang et al, 2007;Petroni et al, 2010;Rusnak, Janciak, Majdan, Wilbacher, & Mauritz, 2007;Selladurai, Jayakumar, Tan, & Low, 1992;Stranjalis et al, 2008;Turazzi, Bricolo, & Pasut, 1984;Turazzi, Bricolo, Pasut, & Formenton, 1987). A flow diagram of the selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation